La peur chez les névrosés dans l’œuvre zolienne - Doua Oulaï, Monné Caroline (Romanica Silesiana)
Fear has always entered the human soul. Aware of this fact, Emile Zola speaks of this emotion in his fictional works, especially his neurotic characters. Thus, either the “crazies”, victims of the breakdown of the time, real hysterical, religious neurosis or the “irregulars of hysteria” and “doubles” of Zola, all are animated by a neurotic, even hysterical fear. Speaking of fear in his neuroses, Zola speaks of his own fears related to his neurosis. Furthermore, the writer offers a remedy to the neurotic fear, remedy that occurs through the pipe of the passions. Key words: fear, neurosis, hysteria, Second Empire